Social Advocacy as an Effort to Help Problems Faced by Children in Conflict with the Law - Nufus, Belgis Hayyinatun (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2025)
The existence of 133 cases of Children in Conflict with Law (ABH) in Jember Regency from 2023-March 2025 shows the need for serious handling involving various parties. So far, the Nurul Huda Correctional Care Community Group (Pokmas Lipas) has taken part in overcoming the very complex problem of ABH. Still, the participation cannot be maximized because the Pokmas Lipas has limitations. Keris WeSave as one of the elements of society from the academic element also took a role in this matter, starting with identifying urgent issues to be overcome, identifying the potential of ABH and Pokmas Lipas, identifying stakeholders who are willing to collaborate. From the problems identified, WeSave intervened in the form of social advocacy for ABH through FGD to build a social network with stakeholders and active learning methods for digital marketing training for ABH. The social advocacy has succeeded in overcoming several urgent problems faced by ABH.